Control‎ ‎and‎ ‎Synchronization‎ ‎of‎ a‎ ‎Chaotic Memristor System Based on Graphical Approach - Marzieh Pabasteh; Bashir Naderi (Mathematics Interdisciplinary Research, 2025)
‎In this article‎, ‎we analyze a four-dimensional chaotic system‎, ‎focusing on bifurcation and the Lyapunov exponent as key characteristics under new parameter settings‎. ‎Our main goal is to control the system using a graphical algorithm based on contraction method in dynamical systems‎. ‎The controller designed using this method is simpler than most controllers for chaotic systems‎. ‎Since chaotic systems are sensitive to initial conditions‎, ‎their synchronization and control are essential challenges‎. ‎The graphic algorithm is used for both controlling and synchronizing the chaotic memristor system‎. ‎Also‎, ‎we utilize the synchronization results for secure communication‎, ‎employing master and slave systems as encryption and decryption keys‎. ‎The effectiveness of the proposed method is demonstrated through numerical simulations‎.